Widespread Deregulation of Phosphorylation-Based Signaling Pathways in Multiple Myeloma Cells: Opportunities for Therapeutic Intervention - Fuhler, Gwenny Manel (ScholarOne, 2011)
Multiple myeloma (MM) is a neoplasm of plasma cell origin that is largely confined to the bone marrow (BM). Chromosomal translocations and other genetic events are known to contribute to deregulation of signaling pathways that lead to transformation of plasma cells and progression to malignancy. However, the tumor stroma may also provide trophic support and enhance resistance to therapy. Phosphorylation of proteins on tyrosine, serine and threonine residues plays a pivotal role in cell growth and survival. Therefore, knowing the status of phosphorylation-based signaling pathways in cells may provide key insights into how cell growth and survival is promoted in tumor cells. To provide a more comprehensive molecular analysis of signaling disruptions in MM, we conducted a kinome profile comparison of normal plasma cells and MM plasma cells as well as their surrounding cells from normal BM and diseased BM. Integrated pathway analysis of the profiles obtained reveals deregulation of multiple signaling pathways in MM cells but also in surrounding bone marrow blood cells compared to their normal counterparts. The deregulated kinase activities identified herein, which include the mTOR (mammalian target of rapamycin)/p70S6K and ERK1/2 (extracellular signal-regulated kinases 1 and 2) pathways, are potential novel molecular targets in this lethal disease.